Use of toothpaste in peruvian children under 12 years old, during the period of 2016 - 2018. Results of a national survey - Diaz Soriano, Ana (2021)
Objective: To report the use of toothpaste in Peruvian children under 12 years old, during the period of 2016 - 2018. Materials and methods: The study was descriptive, longitudinal and retrospective, using the records of the ENDES database, Peru, during 2016-2018. The sample was multistage, probabilistic and stratified, consisting of 118,716 records of children under 12 years of age. The variables were: use of toothpaste, fluoride concen-tration, department, geographical area and natural region. A descriptive analysis of the absolute and relative frequencies was performed. Results: Of the participants, they brushed their teeth, 88%; they brush their teeth 2 times a day, 40%; they used toothpaste, 98%; they used toothpaste with a fluorine concentration of 1000ppm or more, 44.6% (n = 15 376), 43.2% (n = 14 545) and 44% (n = 16 227), for the years 2016, 2017 and 2018, respectively. In the departments of Piura, Loreto, San Martin and Ucayali use toothpaste ≥1000ppm of fluoride, in a greater percentage, in a 55% to 74.9%. Dental creams with ≥1000ppm of fluoride were more used in the jungle region and urban areas. Conclusions: The population was found to brush their teeth, twice a day and use toothpaste; However, less than half of Peruvians under 12 years of age use fluoridated toothpaste with 1000 ppm or more. These results could be related to current preventive policies against tooth decay.